1997
DOI: 10.1212/wnl.48.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Processing in Primary Headache

Abstract: There is a loss of cognitive habituation in migraine, which may serve as a specific but not sensitive diagnostic tool. The pathophysiologies of migraine and cluster headache have a specific modifying property on cognitive processing reflected by a loss of cognitive habituation or an increased cognitive processing time. These effects can, in part, be counterbalanced by antimigraine medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
97
2
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 13 publications
11
97
2
7
Order By: Relevance
“…[34][35][36][37][38][39][40][41][42][43] The first evidence for altered interictal habituation in patients with migraine came from studies of contingent negative variation (CNV), a slow event related corti cal response representing higher mental functions. [44][45][46][47] Subsequently, deficient habituation was demonstrated for another event related potential, P300, which is eli cited in the process of decision making after visual 48 or auditory 49,50 stimulation. Deficient habitu ation was also subsequently described for several other modality specific evoked potentials: pattern reversal visual evoked potentials (VEPs), [33][34][35][36][37][38][39][40][41][42] visual evoked magneto encephalographic (MEG) responses, 43 auditory evoked potentials (AEPs), 51,52 and somatosensory evoked poten tials (SSEPs).…”
Section: Impaired Habituationmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37][38][39][40][41][42][43] The first evidence for altered interictal habituation in patients with migraine came from studies of contingent negative variation (CNV), a slow event related corti cal response representing higher mental functions. [44][45][46][47] Subsequently, deficient habituation was demonstrated for another event related potential, P300, which is eli cited in the process of decision making after visual 48 or auditory 49,50 stimulation. Deficient habitu ation was also subsequently described for several other modality specific evoked potentials: pattern reversal visual evoked potentials (VEPs), [33][34][35][36][37][38][39][40][41][42] visual evoked magneto encephalographic (MEG) responses, 43 auditory evoked potentials (AEPs), 51,52 and somatosensory evoked poten tials (SSEPs).…”
Section: Impaired Habituationmentioning
confidence: 99%
“…Taken together, the dysfunctions found in the migrainous brain suggest an impairment of thalamo cortical control of temporal activation of different neuronal networks. 48 Thalamocortical dysrythmia has also been pro posed to underlie other functional brain disorders. 140,141 In patients with chronic neuropathic pain, over activation in the theta and beta range -suggestive of thalamocortical dysrhythmia-was found in the corti cal 'pain matrix' .…”
Section: Thalamocortical Dysrhythmia In Migrainementioning
confidence: 99%
“…2,6,11 In contrast, these anomalies are not observed during the migraine attack. 9 Habituation to a stimulus is generally thought to be one of the most basic forms of learning and also thought to protect the brain from information overload. 11 As such, it has been suggested that the migraine attack is a protective vascular response to this potential information overload, particularly in the left hemisphere of the brain where verbal capac-ity may be limited.…”
Section: Figure 2 the Mean Verbal Iq Scores Across Four Childhood Amentioning
confidence: 99%
“…Functional and electrophysiologic alterations in cortical functioning have been found during the migraine interval, [1][2][3][4][5] which may be associated with cognitive impairment as demonstrated on tests of perception, 6,7 psychomotor ability, 8 attention, [9][10][11] and verbal memory. 12,13 However, not all studies have found such cortical alterations 14 or cognitive performance decrements.…”
mentioning
confidence: 99%
See 1 more Smart Citation